Research of marketing and pharmacoeconomic aspects of the domestic market of preparations used for biorevitalization - N. O. Tkachenko; N. M. Chervonenko; V. O. Demchenko; O. V. Lytvynenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the work is to study the Ukrainian market for biorevitalization products with the subsequent formation of an information array, which can be used to improve the system for supplying target consumers and for correct strategic marketing decision-making.